(untitled) (Research, Society and Development, 2025)
The mature ovarian cystic teratoma is the most common type of benign ovarian tumor in women. Diagnosis is frequently incidental, performed through imaging exams such as ultrasonography, computed tomography, and magnetic resonance imaging (MRI), or during surgical procedures. Treatment varies based on the patient’s individual characteristics. As the main objective, analyze the importance of magnetic resonance imaging (MRI) in the accurate diagnosis of mature pelvic teratomas, contributing to the understanding of the efficacy of this imaging technique in evaluating this rare condition. It is about a descriptive study with a qualitative approach, based on a case report conducted at the Patos University Center.The sample consisted of a female patient residing in Patos, Paraíba, diagnosed with a mature pelvic teratoma at the age of 16 years and 4 months. Concluded that treatment selection should consider the individual characteristics of each patient as well as specific tumor features, which vary from case to case. In the case reported, an MRI was performed, clearly revealing the condition and enabling the development of the most effective treatment plan.